2019
DOI: 10.1080/15459624.2018.1540877
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter hood contamination: Efficiency of laundering to remove PAHs and FRs

Abstract: Firefighters are occupationally exposed to products of combustion containing polycyclic aromatic hydrocarbons (PAHs) and flame retardants (FRs), potentially contributing to their increased risk for certain cancers. Personal protective equipment (PPE), including firefighter hoods, helps to reduce firefighters' exposure to toxic substances during fire responses by providing a layer of material on which contaminants deposit prior to reaching the firefighters skin. However, over time hoods that retain some contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Similarly, FR-containing furniture may add to the toxic burden of fighting fires and translate to higher exposures among firefighters when they respond to fires. Studies have shown that fighting fires can contaminate firefighter gear, trucks, engines and equipment, bringing chemical exposures indoors (Banks et al 2020; Mayer et al 2019; Shen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, FR-containing furniture may add to the toxic burden of fighting fires and translate to higher exposures among firefighters when they respond to fires. Studies have shown that fighting fires can contaminate firefighter gear, trucks, engines and equipment, bringing chemical exposures indoors (Banks et al 2020; Mayer et al 2019; Shen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, firefighter gear may still contain FR compounds that can additionally contribute to exposures from dust accumulated on the gear from fires and calls (Alexander and Baxter 2016). A recent study of firefighting gear found that fighting fires may contaminate the hoods firefighters wear under their protective equipment with OPFRs (Mayer et al 2019). Additionally, laundering may have a limited impact on reducing exposures and, in some cases, may cross-contaminate gear (Mayer et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, os Retardantes de chama bromados estão associados a casos de câncer em bombeiros. (Mayer et al, 2019).…”
Section: Exposição à Fumaçaunclassified
“…Recent studies [ 11 , 12 ] highlight the importance of proper cleaning of turnout gear as carcinogens can persist and accumulate in clothing, leading to continuous exposure outside of firefighting situations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%